Quran's Method of Changing Thoughts and Concepts Ibn-Abbas' Answer to the Kharijites' Thought Model (Islamic Sciences Journal, 2023)
ABSTRACT                    The Qur'anic approach to changing ideas and concepts wants a person to obtain self-conviction based on argument and evidence, in the context of a quiet and deep dialogue. For every question a person faces an answer that guides him to the straight path. The one who looks at the book of Allah finds this in many models and situations, between the Creator and the creature, and between the prophets and their people, but we dealt with a living model that we can benefit from in our contemporary reality, showing us how to respond to some extremist visions and concepts stemming from a superficial understanding of the Qur’anic text, through the  responses of Ibn Abbas May Allah be pleased with them both on the thought of the Kharijites. The title was: (The Qur’anic Approach to Change Ideas and Concepts, Ibn Abbas’s Responses to the Thought of the Kharijites as a Model)
Keywords: Approach - change - ideas - concepts - Kharijites.